Cranioplasty Using Polymethylmethacrylate Cement Following Retrosigmoid Craniectomy Decreases the Rate of Cerebrospinal Fluid Leak and Pseudomeningocele. Issue 2 (March 2019) - Ou, Changjiang; Chen, Yili; Mo, Jun; Wang, Shenghu; Gai, Shiying; Xing, Ruxin; Wang, Bo; Wu, Chunlai
Abstract : Objective: Cerebrospinal fluid (CSF) leak frequently occurs after retrosigmoid craniectomy. The present study investigated the effects of cranioplasty using polymethylmethacrylate (PMMA) cement to reduce the incidence of CSF leak following retrosigmoid craniectomy as compared with the autologous bone flap combined with titanium plates. Methods: Two hundred forty-three patients underwent surgeries via retrosigmoid approach for microvascular decompression or tumor resection. Of these, 107 patients underwent craniotomy, and incomplete cranioplasty was performed with autologous bone flap fixed with titanium plates, while 136 patients underwent craniectomy and complete cranioplasty was performed with PMMA cement. Variables including the incidence of CSF leak, pseudomeningocele formation, wound infection, rejection reaction were compared retrospectively based on the clinical data between the 2 groups. Results: In the autologous bone group, 9 patients had postoperative CSF leaks, and 11 patients had pseudomeningoceles, while 3 CSF leaks and 2 pseudomeningoceles were found in the PMMA group. Statistical analysis showed that PMMA significantly decreased the incidence of postoperative CSF leaks ( P  = 0.03) and pseudomeningocele formation ( P  = 0.002). Wound infections were observed in 2 and 1 patients between the autologous bone and PMMA group, respectively, which did not differ significantly ( P  = 0.58). None of the patients in both groups developed a rejection reaction of artificial materials. Conclusions: Complete cranioplasty with PMMA cement following retrosigmoid craniectomy could decrease the incidence of CSF leak and pseudomeningocele formation as compared with the autologous bone flap combined with titanium plates. Thus, PMMA cement is preferable for bone reconstruction with excellent biocompatibility and without increasing the rate of wound infection. Abstract : Supplemental Digital Content is available in the text